Students' green perception and behavior / Siti Norashikin Bashirun ... [et al.] - Siti Norashikin Bashirun, Bashirun; Nur Idayu, Badrolhisam; Farah Shazlin, Johari; Nurhafizah, Mohd Zolkapli; Nor Maslia, Rasli Samudin; Nur Faithzah, Jamian (Universiti Teknologi MARA, Perak, 2016)
This study examined how student at UiTM Bandaraya Melaka perceived green practices. Convenient sample of 200 respondents were surveyed. Students have positive perception towards green and findings show there is no significant difference on perception and there is significant difference in doing green activity. Result indicated that “recycle paper” is the most chosen activity done by respondents whereas “attending green conference” is the least activity respondent chose to get involve. The implications of this study are useful to student’s association; university and environmental organization as a guideline to organize green activities and to motivate students participate actively in green practices.